Predicting optic atrophy in patients with anterior uveitis by computed tomography-based assessment of optic nerve diameter - L.V. Venger; O.V. Kovtun; V.V. Savko (Ukrainian Society of Ophthalmologists, 2023)
Background: An objective assessment of factors for ocular inflammation and its sequelae and diagnostic assessment of possible development of the sequelae in early phases of uveitis are essential for early and effective treatment of endogenous uveitis. Purpose: To determine whether it is possible to predict optic atrophy in patients with anterior uveitis using computed tomography (CT)-based assessment of optic nerve diameter. Material and Methods: Patients with anterior uveitis underwent a routine eye examination (ophthalmoscopy, biomicroscopy, intraocular pressure (IOP) measurement, and Humphrey perimetry). In addition, they underwent CT-based assessment of optic disc diameter at 3-5 mm from the entrance into the orbit in the affected eye and the contralateral healthy eye. Patients received treatment as per the protocol. Results: The percentage difference in optic nerve diameter between patients with uveitis complicated by optic neuritis and those with uveitis only for affected eyes was large (33.1%) and statistically significant. At 3 months and 6 months after initiation of treatment, mean optic disc diameter in patients with optic neuritis decreased by 37.2% and 49.1%, respectively, compared to baseline values. At 6 months, a decrease in optic nerve diameter among optic neuritis patients was observed both in those who received treatment and in those who failed to receive treatment, but was less marked in the former patients. Particularly, from 3 months to 6 months, optic nerve diameter decreased by 17.3% in treated optic neuritis patients versus 23.5% in those who remained untreated. Conclusion: CT-based data on the change in the optic nerve diameter at the entrance into the orbit in patients with optic neuritis is an objective characteristic of the presence and grade of atrophic process. Early identification of the potential for development of optic atrophy in individuals with optic neuritis will make it possible to treat them early and, consequently, to prevent or stabilize the process.